Lyophilization-free proliposomes for sustained release oral delivery of hydrophobic drug (cinnarazine): a comparative study - Abu Abed Omar S.; Mulkala Srilikha; Sharif Israa; Abdin Asma M.; Elkordy Amal A. (De Gruyter, 2021)
Cinnarizine is used for the treatment of vestibular disorders. However, its poor solubility limits its clinical uses due to many challenges. Liposomes were utilised to improve the release profile of many poorly soluble drugs. However, liposomes face many stability challenges during the storage period. This study aims to develop proliposomes designed for the oral delivery of cinnarizine with enhanced stability characteristics.